STAT3 Regulates Lytic Activation of Kaposi's Sarcoma-Associated Herpesvirus - King, Christine A. (J Virol, 2015)
Lytic activation of Kaposi's sarcoma-associated herpesvirus (KSHV) from latency is a critical contributor to pathogenesis and progression of KSHV-mediated disease. Development of targeted treatment strategies and improvement of lytic-phase-directed oncolytic therapies, therefore, hinge on gaining a better understanding of latency-to-lytic-phase transition. A key observation in that regard, also common to other herpesviruses, is the partial permissiveness of latently infected cells to lytic-cycle-inducing agents. Here, we address the molecular basis of why only some KSHV-infected cells respond to lytic stimuli. Since cellular signal transducer and activator of transcription 3 (STAT3) is constitutively active in KSHV-associated cancers, KSHV activates STAT3, and STAT3 has been found to regulate lytic activation of Epstein-Barr virus (EBV)-infected cells, we asked if STAT3 contributes similarly to the life cycle of KSHV. We found that high levels of STAT3 correlate with the refractory state at the single-cell level under conditions of both spontaneous and induced lytic activation; importantly, STAT3 also regulates lytic susceptibility. Further, knockdown of STAT3 suppresses the cellular transcriptional corepressor Krüppel-associated box domain-associated protein 1 (KAP1; also known as TRIM28), and suppression of KAP1 activates lytic genes, including the viral lytic switch RTA, thereby linking STAT3 via KAP1 to regulation of the balance between lytic and latent cells. These findings, taken together with those from EBV-infected and, more recently, herpes simplex virus 1 (HSV-1)-infected cells, cement the contribution of host STAT3 to persistence of herpesviruses and simultaneously reveal an important lead to devise strategies to improve lytic-phase-directed therapies for herpesviruses. IMPORTANCE Lytic activation of the cancer-causing Kaposi's sarcoma-associated herpesvirus (KSHV) is vital to its life cycle and causation of disease. Like other herpesviruses, however, a substantial fraction of latently infected cells are resistant to lytic-phase-inducing stimuli. Investigating the molecular basis for this refractory state is essential for understanding how the virus persists and how it causes disease and to guide efforts to improve treatment of KSHV-mediated diseases. We found that, like two other herpesviruses, EBV and HSV-1, KSHV exploits the cellular transcription factor STAT3 to regulate the susceptibility of latently infected cells to lytic triggers. These findings highlight a common STAT3-centered strategy used by herpesviruses to maintain persistence in their hosts while also revealing a key molecule to pursue while devising methods to improve herpesvirus lytic-phase-directed therapies.